A CCD vertex detector for a high-energy linear e(+)e(-) collider - Burrows, P (Elsevier, 2000)
I present a summary of the experience with CCD-based vertex detectors at the SLD experiment at SLAG. and discuss their advantages for use at a future high-energy linear e(+)e(-) collider. The extensive RandD programme to improve further the vertexing capabilities of CCD detectors is also outlined. (C) 2000 Elsevier Science B.V. All rights reserved.